1991
DOI: 10.1111/j.1476-5381.1991.tb12250.x
|View full text |Cite
|
Sign up to set email alerts
|

Deamination of newly‐formed dopamine in rat renal tissues

Abstract: 1 The present study has examined the formation of dopamine and 3,4-dihydroxyphenylacetic acid (DOPAC) in slices of the rat renal cortex and the renal medulla loaded with exogenous L-fl-3,4-dihydroxyphenylalanine (L-DOPA). The effects of pargyline and of two selective inhibitors of monoamine oxidase (MAO) types A and B, respectively Ro 41-1049 and Ro 19-6327, on the deamination of newlysynthesized dopamine in kidney slices incubated with exogenous L-DOPA were also tested. The assay of L-DOPA, dopamine, noradren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

1994
1994
2011
2011

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 19 publications
(27 reference statements)
2
22
0
Order By: Relevance
“…Of course it could be argued also that the lack of effect of MAO inhibitors in reducing the tissue accumulation of DOPAC is a concentration-related problem. In our hands, however, when added to the incubation medium before loading with L-DOPA, all the three MAO inhibitors, at these very same concentrations, were found to decrease DOPAC formation (100pM pargyline, 84% reduction; 250 nM Ro 41-1049, 86% reduction; 250 nM Ro 19-6327, 79% reduction) Fernandes et al, 1991). The deamination of newly-formed dopamine in kidney slices loaded with exogenous L-DOPA is rather unlikely to occur in a neuronal compartment.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…Of course it could be argued also that the lack of effect of MAO inhibitors in reducing the tissue accumulation of DOPAC is a concentration-related problem. In our hands, however, when added to the incubation medium before loading with L-DOPA, all the three MAO inhibitors, at these very same concentrations, were found to decrease DOPAC formation (100pM pargyline, 84% reduction; 250 nM Ro 41-1049, 86% reduction; 250 nM Ro 19-6327, 79% reduction) Fernandes et al, 1991). The deamination of newly-formed dopamine in kidney slices loaded with exogenous L-DOPA is rather unlikely to occur in a neuronal compartment.…”
Section: Discussionmentioning
confidence: 95%
“…Although this does not completely rule out the possibility that some of the renal dopamine might have access to neuronal MAO, there is evidence to suggest that the neuronal uptake of newly-formed dopamine in kidney slices is most probably an irrelevant process. When levels of dopamine in kidney slices increase up to 480 nmol g-' (i.e., 6000 fold the levels of endogenous dopamine), as has found to occur in the presence of 2.5 mM L-DOPA, the levels of endogenous noradrenaline (1.3 nmol g') in kidney slices do not change (Fernandes et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Firstly, most of renal MAO appears to be located extraneuronally (Caramona & Soares-da-Silva, 1990;Soares-da-Silva et al, 1992a). Secon&b ly, it has been shown that the levels of noradrenaline in kidney slices did not change when up to 2500fiM L-DOPA was added to the incubation medium, thus suggesting that the dopamine formed in renal tissues loaded with L-DOPA has no access to nerve terminals (Fernandes et al, 1991). If the released dopamine is in fact subject to an uptake process into the tubular cells, it might be suggested that this is most likely to occur at the basolateral cell border of tubular cells, namely when using kidney slices.…”
Section: Resultsmentioning
confidence: 99%